2005
DOI: 10.3171/ped.2005.103.2.0163
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 3-tesla magnetic resonance imaging on various pressure programmable shunt valves

Abstract: The Sophy Polaris valve allows shunt-dependent patients who need a programmable valve to undergo 3-tesla MR imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 10 publications
1
22
0
Order By: Relevance
“…We consider major complications those requiring surgical correction, including subdural hematomas and empyemas, permanent shunt obstruction and shunt infection. We consider minor complications those in which the adjustment of pressure and clinical measures were sufficient and effective for the control, including wound dehiscence, slit ventricle syndrome, transient shunt obstruction and resetting after MRI procedures 20,21 (Table 2). …”
Section: Complicationsmentioning
confidence: 99%
“…We consider major complications those requiring surgical correction, including subdural hematomas and empyemas, permanent shunt obstruction and shunt infection. We consider minor complications those in which the adjustment of pressure and clinical measures were sufficient and effective for the control, including wound dehiscence, slit ventricle syndrome, transient shunt obstruction and resetting after MRI procedures 20,21 (Table 2). …”
Section: Complicationsmentioning
confidence: 99%
“…Authors of several studies have established that MR imaging can alter the valve settings on programmable valves regardless of their initial settings [4,6,8,9]. Accidental resetting induced by an external magnetic field other than those associated with MR imaging has been reported to be rare [11].…”
Section: Discussionmentioning
confidence: 99%
“…However, unintended pressure changes in programmable valves can also be caused by external magnetic fields. Alterations in valve settings are common after exposure to strong magnetic fields such as those involved in magnetic resonance (MR) imaging, and the need for readjustment of the valve setting after MR imaging has been emphasized in the neurosurgical and neuroradiological literature [4,6,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Earlier research completed on the safety of programmable valves in MRI demonstrated no effect on valve function at 3T. 70 More recent data, however, has demonstrated some effects due to the electromagnetic field, resulting in a ''conditional" safety classification, as no permanent damage to valve function has actually been noted. A slight increase in temperature has been reported of the order of 0.4 degrees C. However, even though the shunt valve may be safe for MRI, the valve settings can change during imaging, necessitating resetting of the valve.…”
Section: Devices and Foreign Bodiesmentioning
confidence: 95%